Ever-widening Circles: consolidating and enhancing Wirlomin Noongar archival material in the community - Bracknell, Clint; Scott, Kim (Sydney University Press, 2020)
Returning archival documentation of endangered Indigenous languages to their community of origin can provide empowering opportunities for Indigenous people to control, consolidate, enhance, and share their cultural heritage with ever-widening, concentric circles of people, while also allowing time and space for communities to recover from disempowerment and dislocation. This process aligns with an affirming narrative of Indigenous persistence that, despite the context of colonial dispossession, can lead to a positive, self-determined future. In 2007, senior Noongar of the Wirlomin clan in the south coast region of Western Australia initiated Wirlomin Noongar Language and Stories Inc., an organisation set up to facilitate cultural and linguistic revitalisation by combining community-held knowledge with documentation and recordings repatriated from the archives. Fieldnotes created in 1931 from discussions with local Aboriginal people at Albany, Western Australia have inspired the collaborative production of six illustrated bilingual books. Working with archival research material has presented challenges due to issues of orthography and legibility in written records, the poor quality of audio recordings, and the incomplete documentation of elicitation sessions. As the archive is so fragmentary, community knowledge is vital in making sense of its contents.